2014
DOI: 10.1166/jnn.2014.10174
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Polymeric Dispersant Concentration for the Dispersion-Stability of Magnetite Nanoparticles in Water Solution

Abstract: Fouling of various Fe oxide particulates on heat transfer tubes in the coolant of the secondary system of a nuclear power plant has been known to reduce the heat transfer performance and degrade the integrity of system components. Thus, in order to mitigate such a fouling problem, an addition of polymeric dispersant has been proposed to remove the oxide partculates. In this paper, experimental studies was conducted for evaluating the effect of polymeric dispersants (PAA: Polyacrylic acid, PMA: Polymethacrylic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Other polymeric dispersants (PAA: polyacrylic acid, PMA: polymethacrylic acid, PAAMA: polymaleic acid-co-acrylic acid) on the dispersion stability of MNPs have been investigated by the settling test, the transmittance, zeta-potential, and particle size measurements. It is observed that the critical concentration for maximizing the dispersion stability of MNPs is in the range of concentration ratio (dispersant/MNPs) of 0.1 to 0.01 and the dispersion-stability of MNPs is not improved when the dispersant concentration is above this critical value [97].…”
Section: Fate Transport and Toxicity In The Environment 31 Dispermentioning
confidence: 99%
“…Other polymeric dispersants (PAA: polyacrylic acid, PMA: polymethacrylic acid, PAAMA: polymaleic acid-co-acrylic acid) on the dispersion stability of MNPs have been investigated by the settling test, the transmittance, zeta-potential, and particle size measurements. It is observed that the critical concentration for maximizing the dispersion stability of MNPs is in the range of concentration ratio (dispersant/MNPs) of 0.1 to 0.01 and the dispersion-stability of MNPs is not improved when the dispersant concentration is above this critical value [97].…”
Section: Fate Transport and Toxicity In The Environment 31 Dispermentioning
confidence: 99%